Hubungan antara Kecerdasan Moral dengan Sikap pada Ujaran Kebencian pada Pengguna Media Sosial di Indonesia - Prasetiya, Juli Angga (Jurnal Psikologi : Media Ilmiah Psikologi, 2019)
The rise of hate speech in social media has become a serious issue in Indonesia. With a massive number of users, social media has become an effective and almost unlimited means of spreading hate speech. A positive attitude towards hate speech will deepen the conflict that occurs as a result of hate speech. Individuals must be able to take a stand based on the belief in the truth of the information received. For this reason, moral intelligence is needed so that in facing the utterance of hate individuals have an understanding of right and wrong which are the basic principles of strong character so that individuals do not support the utterance of hatred. This research aims to determine the relationship between moral intelligence and attitudes toward hate speech. The research design used is quantitative correlational. The research sample is using non-probability sample with purposive sampling techniques as many as 100 social media users in Indonesia. Measuring instrument for moral intelligence is based on Borba's theory (2001) with 49 valid items and reliability coefficient (a) 0.922. Measuring instrument for attitudes toward hate speech is based on Azwar's theory (2008) with 12 valid items and reliability coefficient (a) 0.762. This research result shows a significant negative relationship sig 0.000 and r -0.358) between moral intelligence and attitudes toward hate speech. Moral intelligence contributes 12.8% to attitudes toward hate speech. More of social media users’ moral intelligence are low (53%), while more of the attitudes toward hate speech are negative (59%). The results of the cross tabulations show that there is a relationship between the latest education with attitudes toward hate speech, and there is a relationship between the duration of social media usage per day with moral intelligence.  Keywords: Moral Intelligence, Attitudes Toward Hate Speech, Social Media